2004
DOI: 10.1583/1545-1550(2004)011<0033:hmpwia>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

How Many Patients With Infrarenal Aneurysms Are Candidates for Endovascular Repair?The Northern California Experience

Abstract: Fifty-five percent of patients considered for endovascular AAA repair in community hospitals in Northern California met the anatomical selection criteria for the AneuRx stent-graft. Men appeared to be twice as likely to meet the eligibility requirements as women. Unfavorable infrarenal neck anatomy was the primary exclusion criterion for endovascular repair in this community setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 18 publications
0
62
0
Order By: Relevance
“…Our technical success rate was 100%, which compares favorably with the reported rates of 94% to 99% for various other endografts. [42][43][44][45][46][47][48][49][50][51] An interesting observation during follow-up Ͼ60 months is that no procedure related complication developed after postoperative day 30 in any of the patients for whom long-term data were available. Endoleak from the site of the occluded iliac artery may also theoretically occur when an aortomonoiliac graft is used; however, this complication was not documented in our patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Our technical success rate was 100%, which compares favorably with the reported rates of 94% to 99% for various other endografts. [42][43][44][45][46][47][48][49][50][51] An interesting observation during follow-up Ͼ60 months is that no procedure related complication developed after postoperative day 30 in any of the patients for whom long-term data were available. Endoleak from the site of the occluded iliac artery may also theoretically occur when an aortomonoiliac graft is used; however, this complication was not documented in our patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the inflexibility of externally supported grafts, this segment of the aorta must not be severely angulated. This requirement may impose a gender bias in patient selection, because in addition to the fact that their small external iliac arteries often present problems with respect to vascular access, women also appear to have a higher prevalence of short, angulated aneurysm necks than men (1138,1139). Considering all of these criteria, Carpenter et al reported that a disproportionate number of women were excluded from endograft repair because of anatomic limitations (60% of women vs. 30% of men; p equals 0.0009) (1140).…”
Section: Introductionmentioning
confidence: 99%
“…Operative Mortality and Postoperative Complication Rates for Open Repair of Pararenal, Suprarenal, and/or Type IV Thoracoabdominal Aortic Aneurysms, Since 1990 ACC/AHA Guidelines for the Management of PAD men(366,367). Considering all of these criteria, Carpenter et al reported that a disproportionate number of women were excluded from endograft repair because of anatomic limitations (60% of women vs. 30% of men; p equals 0.0009)(368).Becker et al (369) also found that significantly fewer women qualified for endovascular aneurysm repair (26% of women vs. 41% of men), and Mathison et al…”
mentioning
confidence: 99%